2016
DOI: 10.1111/epi.13571
|View full text |Cite
|
Sign up to set email alerts
|

Remembrance and time passed: Memory outcomes 4–11 years after pediatric epilepsy surgery

Abstract: Patients who became seizure-free had some advantages in memory, but did not show improvements over time. These findings have important implications for understanding potential outcomes from surgery or continued use of antiepileptic medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…[19][20][21][22][23] In long-term follow-up (mean postoperative period of 7 years), poorer story recall scores have been documented for children with left TLE compared to those with right TLE. 24 Another study showed that at a mean of 9 years postoperatively, verbal memory outcome was comparable between children who underwent left TLE, right TLE, and children with TLE treated pharmacologically. 23 It is possible that the potential deleterious effects of early surgical intervention are mitigated by greater brain plasticity in childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23] In long-term follow-up (mean postoperative period of 7 years), poorer story recall scores have been documented for children with left TLE compared to those with right TLE. 24 Another study showed that at a mean of 9 years postoperatively, verbal memory outcome was comparable between children who underwent left TLE, right TLE, and children with TLE treated pharmacologically. 23 It is possible that the potential deleterious effects of early surgical intervention are mitigated by greater brain plasticity in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In children, there have been mixed findings for verbal memory outcome after left temporal lobectomy; declines in memory have been reported in some studies, but not in others . In long‐term follow‐up (mean postoperative period of 7 years), poorer story recall scores have been documented for children with left TLE compared to those with right TLE . Another study showed that at a mean of 9 years postoperatively, verbal memory outcome was comparable between children who underwent left TLE, right TLE, and children with TLE treated pharmacologically .…”
mentioning
confidence: 99%
“…Within the studies, age at surgery or at presurgical assessment varied from a few months to 18 years. Follow-up after surgery also varied widely, some studies reporting intervals of 4 to 11 years 19,20,22,23 or 0.9 to 15 years, 24 whereas others used fixed intervals of, for example, 2 years. [25][26][27][28] The major aim of most studies was to detect the impact, if any, of epilepsy-related variables on the cognitive outcome measures.…”
Section: Questionsmentioning
confidence: 99%
“…Effects of IQ, DQ, or index (DQ/DI) or a mixture of several approximations of cognitive functioning (among which parental evaluations of their children's adaptive achievements) on targeted cognitive functions were statistically determined in several studies. [19][20][21]25,26,39,44,52 Most of the analyses had an exploratory character without definitive conclusions.…”
Section: Disturbance Of Performances In Tests Of One Function By Defimentioning
confidence: 99%
See 1 more Smart Citation